Cross Cultural Encounters and the Issue of Identity in Tayeb Salih’s Season of Migration to the North - Bourkhis Rima, Merrouche Amani (My University, 2019)
II Abstract Identity and Immigration are among the most prominent themes in postcolonial literature. They are considered to be the chief preoccupation of most contemporary African writers. This study scrutinizes immigration and identity in Tayeb Salih’s Season of Migration to the North. The exploration of such postcolonial writers as Salih in terms of depiction their cultural identities and of their people reveals the hybrid culture of the postcolonial societies and writers. Hence, the study attempts to analyse Salih’s novel in the light of Bhabha’s postcolonial theory of hybridity and ambivalence. Therefore, the purpose of this study is meant to provide a clear analysis of the protagonist’s ongoing struggle in Season of Migration to The North and examine the lost-identity, and its results which are hybridity and ambivalence. As a result one can realise that immigration affected the protagonist to the extent of losing identity.
Keywords: Key words : postcolonialism, hybridity, identity, mimicry, ambivalence.